Special phenyl silicone oil for cosmetics and preparation method thereof
By coating the magnetic core material with organic matter and loading it on a porous silica support, an acidic solid catalyst is formed, which solves the problem of magnetic materials interfering with the reaction in the preparation of phenyl silicone oil, and realizes convenient recovery and efficient catalysis of the catalyst, reducing production costs and improving environmental friendliness.
Patent Information
- Application Number
- CN202411959468.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The prior art is difficult to achieve dense coating treatment for magnetic materials, especially in porous materials, where dense coating and the need to improve the specific surface area and porosity of the carrier are conflicting, and the transition metal iron element in the magnetic material can interfere with the ring-opening copolymerization reaction of phenyl silicone oil.
Magnetic core material containing anionic polymer and coated the surface with organic matter containing cationic polymer to form magnetic particles. Then, these magnetic particles are supported in a porous silica support, and ammonium dihydrogen phosphate is used as a catalyst to form an acidic solid catalyst for easy recycling and recycling.
Effective dense coating of magnetic materials is achieved, contact between magnetic materials and reaction systems is avoided, the convenience of catalyst recycling and catalytic activity is improved, the production cost of phenyl silicone oil is reduced, and the environmental friendliness of the production process is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of daily chemical materials, and in particular to a special phenyl silicone oil for cosmetics and a preparation method thereof. Background Art
[0002] Phenyl silicone oil has good compatibility with cosmetic ingredients, is relatively stable to heat and ultraviolet rays, and has unique gloss, so it is widely used in related fields of cosmetic products.
[0003] In cosmetic products, phenyl silicone oil can be used as an emulsifier and stabilizer. It can form a uniform emulsion between the water and oil phases, help maintain the stability of cosmetics, make cosmetics easier to apply, maintain the uniformity and texture of the product, and lock in moisture, effectively preventing skin moisture loss.
[0004] The preparation of phenyl silicone oil usually uses silane monomer and end-capping agent as raw materials, adds acid catalyst, and obtains the finished product through prepolymerization and ring-opening copolymerization.
[0005] For acid catalysts, inorganic acids or organic acids can generally be used. The acid catalyst can be in the form of a liquid acid catalyst or a solid acid catalyst. Among them, liquid acid catalysts participate in chemical reactions in molecular form, which is not easy to separate from the product in industrial production and difficult to achieve continuous use. In comparison, the active sites of solid acids are attached to solid materials, which can be directly separated by filtration after the reaction and reused. Therefore, solid acid catalysts are a better choice for the preparation process of phenyl silicone oil.
[0006] The requirement for solid acid catalysts is that they need to have a high specific surface area and a three-dimensional interconnected pore structure, and have a high density of active sites. High-density active sites can increase the reaction rate, and high specific surface area can provide a suitable spatial structure for the diffusion of reactants and the conduct of the reaction. In addition, solid catalysts also need to be easy to recycle and recycle. Solid catalysts that meet the above conditions help to increase the rate and yield of the reaction, reduce production costs, and improve the environmental friendliness in the production process.
[0007] Porous solid catalysts in powder or granular form usually have a large specific surface area and a high mass transfer rate, and therefore have a high catalytic activity. In order to facilitate the recovery of powder or granular solid catalysts, the prior art chooses to impart magnetic response properties to the solid catalyst by loading a magnetic material containing iron elements, so as to separate the solid catalyst from the reaction system.
[0008] For example, the Chinese patent with the authorization announcement number CN113663710B provides a method for preparing a magnetic solid acid catalyst, and the Chinese patent with the authorization announcement number CN114100634B provides a method for preparing a magnetic multi-component catalyst.
[0009] From the above analysis, it can be seen that powdered or granular porous solid catalysts that can be separated and recovered using magnetic response characteristics have many technical advantages. However, the shortcomings of the prior art including the above patent documents are that the prior art can only achieve the co-compounding of magnetic materials and catalysts in carrier materials, but it is difficult to achieve dense coating of magnetic materials. Especially for porous materials, the demand for dense coating of magnetic materials is contradictory to the demand for increasing the specific surface area and porosity of the carrier.
[0010] Although the addition of magnetic materials has no effect on some reaction systems, for the preparation process of phenyl silicone oil, the transition metal iron element contained in the magnetic material will interfere with the ring-opening copolymerization reaction of phenyl silicone oil.
[0011] Therefore, how to use magnetic materials to improve the recovery convenience of powder or granular porous solid catalysts, avoid exposure of magnetic materials to the reaction system to affect the ring-opening copolymerization reaction required for the preparation of phenylene silicone oil, and ensure the reaction yield is a technical problem that technicians in this field need to solve. Summary of the invention
[0012] One of the problems solved by the present invention is how to provide an acidic solid catalyst for the production of phenyl silicone oil that is easy to recycle and has a long service life, thereby reducing the production cost of phenyl silicone oil and improving the environmental friendliness of its production process.
[0013] In order to solve at least one of the above problems, the present invention provides a method for preparing a special phenyl silicone oil for cosmetics, the preparation method comprising: S110, performing a prepolymerization reaction using raw materials including trimethyltriphenylcyclotrisiloxane, diphenyl double end cap, and a solid catalyst to obtain a prepolymer; S120, adding diphenyl double end cap to the prepolymer again to carry out a ring-opening copolymerization reaction to obtain a copolymer; S130, distilling the copolymer under reduced pressure to remove low-boiling-point substances, thereby obtaining special phenyl silicone oil; Wherein, the solid catalyst is prepared by the following steps: S210, preparing a magnetic core material containing anionic polymer; S220, coating the surface of the magnetic core material with an organic substance containing a cationic polymer to obtain magnetic particles; S230, preparing a porous silica carrier using a raw material including magnetic particles; S240, loading ammonium dihydrogen phosphate on a porous silica carrier to obtain an acidic solid catalyst.
[0014] In any of the above technical solutions, the mass ratio of trimethyltriphenylcyclotrisiloxane:diphenyl dicapped end:solid catalyst is (80-100):(2-6):(1-3).
[0015] In any of the above technical solutions, S110 specifically includes: S111, adding dehydrated trimethyltriphenylcyclotrisiloxane and a solid catalyst to the first reaction device, heating to 50° C. to 60° C. and stirring evenly; S112. Add 40% to 60% of the total amount of diphenyl double end cap, raise the temperature to 70°C to 75°C and stir the reaction for 2h to 3h to carry out a prepolymerization reaction to obtain a prepolymer.
[0016] In any of the above technical solutions, S120 specifically includes: S121, under the protection of inert gas, transferring the prepolymer and the solid catalyst to a second reaction device, adding the remaining diphenyl double end cap, raising the temperature to 100° C. to 105° C., and stirring the reaction for 3 h to 4 h to allow the prepolymer to undergo a ring-opening copolymerization reaction; S122. After the ring-opening copolymerization reaction is completed, the pH value is adjusted to neutral, and the solid catalyst is recovered to obtain a copolymer.
[0017] In any of the above technical solutions, S130 specifically includes: S131, allowing the copolymer to stand and separate into layers; S132, distilling the copolymer under reduced pressure at 200° C. to 210° C. under a vacuum condition of -0.15 MPa to -0.05 MPa to remove low-boiling point substances, thereby obtaining special phenyl silicone oil.
[0018] In any of the above technical solutions, S210 specifically includes: S211, aminopropyl triethoxysilane, xanthan gum, ethanol and water are uniformly mixed in a mass ratio of aminopropyl triethoxysilane: xanthan gum: ethanol: water = (1-2): (2-4): (5-10): 100, and ferric nitrate is gradually added and stirred until the pH reaches 5 to obtain an iron salt solution; S212, mixing 1,4-diaminobenzene in ethanol in a mass ratio of 1,4-diaminobenzene: sodium hydroxide: ethanol: water = (2-4): (8-10): (10-20): 100, adding sodium hydroxide and water and mixing again to obtain an alkaline solution; S213, adding alkaline solution to the iron salt solution and stirring continuously until the pH value reaches 9, stirring the iron salt solution at a temperature of 85° C. to 95° C. and evaporating in a water bath to obtain iron sol; S214. The iron sol is fed into a reactor and subjected to a hydrothermal treatment for 2.5 to 3 hours at a pressure of 3 MPa to 5 MPa and a temperature of 180°C to 190°C. After the hydrothermal treatment, the solid matter is separated and filtered, washed, and dried to obtain a magnetic core material.
[0019] In any of the above technical solutions, S220 specifically includes: S221. According to the mass ratio of ammonium sulfate: 1,4-benzenedicarboxaldehyde: azo(2-amidinopropane) dihydrochloride: methacryloyloxyethyl trimethyl ammonium chloride: acrylamide: magnetic core material: water = (0.2-0.3): (0.4-1.2): (1-2): (6-8): (6-8): (20-25): 100, 1,4-benzenedicarboxaldehyde, azo(2-amidinopropane) dihydrochloride, methacryloyloxyethyl trimethyl ammonium chloride, acrylamide and water are mixed uniformly, heated to 45° C. to 50° C., ammonium persulfate and magnetic core material are added, kept warm and mixed uniformly again to obtain a first mixture; S222, heating the first mixture to 55° C. to 60° C., and irradiating the first mixture with ultraviolet light for 1.5 h to 2 h using an ultraviolet light source with a wavelength of 254 nm to 365 nm and a power of 600 W to 800 W under simultaneous stirring and heat preservation; S223, after the heating treatment and the ultraviolet light irradiation treatment are completed, the solid matter is separated and filtered, washed, and dried to obtain magnetic particles.
[0020] In any of the above technical solutions, S230 specifically includes: S231, mixing magnetic particles, tetraethyl orthosilicate, ethanol and water in a mass ratio of magnetic particles: tetraethyl orthosilicate: ethanol: water = (10-15): (30-50): (30-50): 100 to obtain a silicon source suspension; S232, by adding sulfuric acid aqueous solution to the silicon source suspension and stirring, the pH value of the silicon source suspension is adjusted to 4 to 5, and stirring is continued for 2.5 hours to 3 hours to obtain a silica sol containing magnetic particles; S233, soaking the silica sol in anhydrous ethanol for aging for 20 to 24 hours to obtain a silica gel containing magnetic particles; S234. Using carbon dioxide as a medium, supercritically drying the silica gel at a temperature of 31° C. to 33° C. and a pressure of 7.3 MPa to 7.5 MPa to obtain a porous carrier.
[0021] In any of the above technical solutions, S240 specifically includes: S241, dissolving ammonium dihydrogen phosphate in water according to a mass ratio of ammonium dihydrogen phosphate: porous carrier: water = (25-30): (30-35): 100, adding the porous carrier, and uniformly dispersing by ultrasonication to obtain a catalyst suspension; S242, evaporating the catalyst suspension to dryness, washing and drying the solid matter to obtain a solid catalyst.
[0022] The present invention also provides a special phenyl silicone oil for color cosmetics, wherein the special phenyl silicone oil is obtained by using the preparation method of any of the above schemes.
[0023] Beneficial Effects The present invention provides a method for preparing a special phenyl silicone oil for color cosmetics. The preparation method uses raw materials including trimethyl triphenyl cyclotrisiloxane, diphenyl double end, and solid catalyst to carry out prepolymerization and ring-opening copolymerization to obtain a copolymer, and then the copolymer is decompressed and distilled to obtain a special phenyl silicone oil. For the purpose of reducing the production cost of phenyl silicone oil and improving the environmental friendliness of its production process, the present invention uses a solid catalyst to promote and catalyze the above reaction. In order to facilitate the recovery and recycling of the solid catalyst, the present invention prepares a catalyst with magnetic response characteristics, and by coating an organic film layer on the surface of the magnetic response material, the magnetic response material is prevented from contacting the reaction system and interfering with the reaction. Through electrostatic adsorption, the film layer containing cationic polymers is uniformly and densely coated on the surface of the magnetic core material containing anionic polymers. In addition, the present invention loads the coated magnetic response material and catalyst on a porous carrier, and uses the characteristics of the porous carrier with high specific surface area and rich pore structure to load the magnetic response material and catalyst, thereby ensuring the catalytic activity, reaction efficiency, and the convenience of catalyst recovery. The porous silica carrier can maintain good mechanical strength and chemical stability in an acidic environment and is a good acidic catalyst carrier. Therefore, the present invention improves the environmental friendliness of the phenyl silicone oil preparation process and reduces its production cost by adopting an improved solid catalyst. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.
[0025] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0026] The present invention provides a method for preparing a special phenyl silicone oil for cosmetics, the preparation method comprising: S110, performing a prepolymerization reaction using raw materials including trimethyltriphenylcyclotrisiloxane, diphenyl double end cap, and a solid catalyst to obtain a prepolymer; S120, adding diphenyl double end cap to the prepolymer again to carry out a ring-opening copolymerization reaction to obtain a copolymer; S130, distilling the copolymer under reduced pressure to remove low-boiling substances to obtain special phenyl silicone oil.
[0027] In the above steps, diphenyl dicapping agent is used as a capping agent. The solid catalyst is specifically an acidic solid catalyst. In terms of mass ratio, trimethyl triphenyl cyclotrisiloxane: diphenyl dicapping agent: solid catalyst = (80-100): (2-6): (1-3).
[0028] The purpose of S110 is to make the raw materials undergo a prepolymerization reaction, and S110 specifically includes: S111, adding dehydrated trimethyltriphenylcyclotrisiloxane and a solid catalyst to the first reaction device, heating to 50° C. to 60° C. and stirring evenly; S112. Add 40% to 60% of the total amount of diphenyl double end cap, raise the temperature to 70°C to 75°C and stir the reaction for 2h to 3h to carry out a prepolymerization reaction to obtain a prepolymer.
[0029] After the prepolymerization reaction is completed, the raw materials need to be subjected to a ring-opening copolymerization reaction, and S120 specifically includes: S121, under the protection of inert gas, transferring the prepolymer and the solid catalyst to a second reaction device, adding the remaining diphenyl double end cap, raising the temperature to 100° C. to 105° C., and stirring the reaction for 3 h to 4 h to allow the prepolymer to undergo a ring-opening copolymerization reaction; S122. After the ring-opening copolymerization reaction is completed, the pH value is adjusted to neutral, and the solid catalyst is recovered to obtain a copolymer.
[0030] After the ring-opening copolymerization reaction is completed, vacuum distillation is required to remove low-boiling substances. S130 specifically includes: S131, allowing the copolymer to stand and separate into layers; S132, distilling the copolymer under reduced pressure at 200° C. to 210° C. under a vacuum condition of -0.15 MPa to -0.05 MPa to remove low-boiling point substances, thereby obtaining special phenyl silicone oil.
[0031] Through the above steps, phenyl silicone oil can be obtained. The present invention adopts a porous acidic solid catalyst to promote the reaction. In order to facilitate the recovery and recycling of the catalyst used in the above reaction, the present invention loads the magnetic response material in the porous solid catalyst. In order to avoid contact between the magnetic response material and the reaction system, the present invention carries out an organic coating treatment on the magnetic core material that exerts the magnetic response effect. Thus, a catalyst that is easy to recycle and has good catalytic activity can be obtained, thereby improving the environmental friendliness of the production of phenyl silicone oil and reducing its production cost.
[0032] Specifically, the solid catalyst is prepared by the following steps: S210, preparing a magnetic core material containing anionic polymer; S220, coating the surface of the magnetic core material with an organic substance containing a cationic polymer to obtain magnetic particles; S230, preparing a porous silica carrier using a raw material including magnetic particles; S240, loading ammonium dihydrogen phosphate on a porous silica carrier to obtain an acidic solid catalyst.
[0033] In the above steps, powder or particles of ferric oxide and / or ferrosoferric oxide can be used as the magnetic core material. The magnetic core material can be obtained by commercial purchase, or by using raw materials such as ferric nitrate or ferric sulfate, such as sol-gel method, hydrothermal method, etc. It can be understood that the nanoscale magnetic core material with uniform particle size distribution prepared by sol-gel method, hydrothermal method, etc. has good magnetic response performance and is a preferred embodiment of the present invention.
[0034] In some implementations of the present invention, S210 specifically includes: S211, aminopropyl triethoxysilane, xanthan gum, ethanol and water are uniformly mixed in a mass ratio of aminopropyl triethoxysilane: xanthan gum: ethanol: water = (1-2): (2-4): (5-10): 100, and ferric nitrate is gradually added and stirred until the pH reaches 5 to obtain an iron salt solution; S212, mixing 1,4-diaminobenzene in ethanol in a mass ratio of 1,4-diaminobenzene: sodium hydroxide: ethanol: water = (2-4): (8-10): (10-20): 100, adding sodium hydroxide and water and mixing again to obtain an alkaline solution; S213, adding alkaline solution to the iron salt solution and stirring continuously until the pH value reaches 9, stirring the iron salt solution at a temperature of 85° C. to 95° C. and evaporating in a water bath to obtain iron sol; S214. The iron sol is fed into a reactor and subjected to a hydrothermal treatment for 2.5 to 3 hours at a pressure of 3 MPa to 5 MPa and a temperature of 180°C to 190°C. After the hydrothermal treatment, the solid matter is separated and filtered, washed, and dried to obtain a magnetic core material.
[0035] In the above steps, S211 uses water-soluble iron nitrate and water as solvent to prepare an iron salt solution. Among them, aminopropyl triethoxysilane is used as a silane coupling agent to reduce the surface energy of the magnetic core material formed subsequently and enhance the coupling between it and organic matter. Xanthan gum is used as an anion modifier to enhance the tightness and uniformity of the connection between the magnetic core material and organic matter. Part of the carboxyl groups of xanthan gum in water will remove hydrogen ions and become anionic groups, so it has anionic properties. Compared with other anionic polymers such as sodium alginate and sodium hydroxymethyl cellulose, the reason why the present invention selects xanthan gum is that it is relatively insensitive to pH value. The wide pH adaptability makes the viscosity of xanthan gum almost unaffected in the range of pH value between 5 and 10, showing a high degree of stability. Even under extreme conditions where the pH value is less than 4 and greater than 11, the viscosity of xanthan gum only changes slightly, so xanthan gum can be evenly dispersed in iron salt solution and iron sol. In an alkaline environment, the iron ions in the iron salt solution combine with hydroxyl groups to form iron hydroxide colloid. The purpose of S212 is to prepare an alkaline solution for reacting with an iron salt solution. It should be noted that alkaline solutions such as sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and ammonia water can all be used to react with an iron salt solution. The present invention selects a mixed solution of ethanol and water of sodium hydroxide, and adds 1,4-diaminobenzene to the sodium hydroxide aqueous solution. The purpose of using ethanol in S212 is to dissolve 1,4-diaminobenzene with weak alkalinity so that it can be evenly dispersed in a mixed solution of ethanol and water. The purpose of S213 is to prepare an iron hydroxide sol containing xanthan gum and 1,4-diaminobenzene. After obtaining the above sol, the present invention chooses to convert iron hydroxide into iron oxide by a hydrothermal method under heating and pressurization conditions. It can be understood that heat treatment exceeding 500°C can also achieve the conversion of iron hydroxide to iron oxide, but in order to protect xanthan gum and 1,4-diaminobenzene, the present invention selects a hydrothermal treatment not exceeding 200°C. In summary, through the above steps, iron oxide doped with xanthan gum and 1,4-diaminobenzene can be obtained, and the present invention uses this as a magnetic core material.
[0036] The purpose of S220 is to coat the surface of the magnetic core material with an organic substance containing a cationic polymer to avoid contact between the magnetic core material and the reaction system of phenyl silicone oil. It can be understood that a uniform, dense and thin film layer is a preferred embodiment of the present invention. In order to obtain a uniform and dense organic film layer, the magnetic core material can be coated with an organic polymer, or an organic monomer can be mixed with the magnetic core material and coated by initiating a polymerization reaction.
[0037] In some implementations of the present invention, S220 specifically includes: S221. According to the mass ratio of ammonium sulfate: 1,4-benzenedicarboxaldehyde: azo(2-amidinopropane) dihydrochloride: methacryloyloxyethyl trimethyl ammonium chloride: acrylamide: magnetic core material: water = (0.2-0.3): (0.4-1.2): (1-2): (6-8): (6-8): (20-25): 100, 1,4-benzenedicarboxaldehyde, azo(2-amidinopropane) dihydrochloride, methacryloyloxyethyl trimethyl ammonium chloride, acrylamide and water are mixed uniformly, heated to 45° C. to 50° C., ammonium persulfate and magnetic core material are added, kept warm and mixed uniformly again to obtain a first mixture; S222, heating the first mixture to 55° C. to 60° C., and irradiating the first mixture with ultraviolet light for 1.5 h to 2 h using an ultraviolet light source with a wavelength of 254 nm to 365 nm and a power of 600 W to 800 W under simultaneous stirring and heat preservation; S223, after the heating treatment and the ultraviolet irradiation treatment are completed, the solid matter is separated and filtered, washed, and dried to obtain magnetic particles.
[0038] In the above steps, the purpose of S221 is to mix the ammonium persulfate initiator, methacryloyloxyethyl trimethylammonium chloride having trimethylammonium groups, and acrylamide with the magnetic core material in an aqueous solvent system to obtain a first mixture in a suspended state. Under heating conditions of 55°C to 60°C, the above monomers undergo a polymerization reaction, and the positively charged amino groups in the above organic matter chemically adsorb with the xanthan gum dopant with anionic characteristics in the magnetic core material, thereby making the polymer uniformly coated on the surface of the magnetic core material. In addition, methacryloyloxyethyl trimethylammonium chloride generates free radicals under ultraviolet light irradiation and the action of azo (2-amidinopropane) dihydrochloride photoinitiator, thereby catalyzing the condensation reaction of the amino group of 1,4-diaminobenzene in the magnetic core material with the aldehyde group of 1,4-benzenedicarbaldehyde to form an imide group. The imide group with good stability can realize the chemical bond between iron oxide and organic matter, improve the uniformity and density of organic coating on the magnetic core material, and improve the chemical stability and thermal stability of the organic film layer, ensuring that under the conditions of the ring-opening equilibrium reaction for preparing phenyl silicone oil, the organic film layer on the surface of the magnetic core material will not be destroyed, thereby avoiding contact between the magnetic core material and the reaction system.
[0039] The purpose of S230 is to load the magnetic particles on a porous carrier. It is understood that porous inorganic materials such as porous ceramics, attapulgite, montmorillonite, hydroxyapatite, halloysite, zeolite, etc. can all be used as solid catalyst carriers. The magnetic particles can be loaded on a porous carrier by mechanically mixing the magnetic particles with the porous carrier and granulating and forming the particles and then sintering them, or by ultrasonic, stirring, wet chemical methods, etc. in the liquid phase so that the magnetic particles are deposited or filled in the pores of the porous carrier.
[0040] In some implementations of the present invention, S230 specifically includes: S231, mixing magnetic particles, tetraethyl orthosilicate, ethanol and water in a mass ratio of magnetic particles: tetraethyl orthosilicate: ethanol: water = (10-15): (30-50): (30-50): 100 to obtain a silicon source suspension; S232, by adding sulfuric acid aqueous solution to the silicon source suspension and stirring, the pH value of the silicon source suspension is adjusted to 4 to 5, and stirring is continued for 2.5 hours to 3 hours to obtain a silica sol containing magnetic particles; S233, soaking the silica sol in anhydrous ethanol for aging for 20 to 24 hours to obtain a silica gel containing magnetic particles; S234. Using carbon dioxide as a medium, supercritically drying the silica gel at a temperature of 31° C. to 33° C. and a pressure of 7.3 MPa to 7.5 MPa to obtain a porous carrier.
[0041] In the above steps, the purpose of S231 is to evenly disperse the magnetic particles in the organic silicon source solution to obtain a suspended magnetic particle silicon source suspension. Using sulfuric acid as a catalyst, a silica gel mixed with magnetic particles can be obtained by a sol-gel method. Through supercritical drying, a porous silica structure can be obtained. Thus, the above steps can obtain a porous silica carrier evenly loaded with magnetic particles.
[0042] In some implementations of the present invention, S240 specifically includes: S241, dissolving ammonium dihydrogen phosphate in water according to a mass ratio of ammonium dihydrogen phosphate: porous carrier: water = (25-30): (30-35): 100, adding the porous carrier, and uniformly dispersing by ultrasonication to obtain a catalyst suspension; S242, evaporating the catalyst suspension to dryness, washing and drying the solid matter to obtain a solid catalyst.
[0043] In the above steps, ammonium dihydrogen phosphate is used as a catalyst, which is loaded on a porous silica carrier containing magnetic particles as a catalyst for driving the catalytic reaction in the preparation process of phenyl silicone oil.
[0044] Embodiment 1 In this embodiment, a series of solid catalyst samples were prepared, and the raw material ratios thereof were shown in Table 1. The preparation process thereof was as follows: S1. Mix KH550 aminopropyl triethoxysilane, xanthan gum, anhydrous ethanol and deionized water in a beaker, gradually add ferric nitrate and stir magnetically at a speed of 300 rpm / min until the pH reaches 5 to obtain an iron salt solution; S2. Mix 1,4-diaminobenzene and anhydrous ethanol in a beaker, add sodium hydroxide and deionized water, and mix again to obtain an alkaline solution; S3, adding alkaline solution to the iron salt solution and continuously stirring the solution with magnetic force at a speed of 180 rpm / min until the pH value is 9, and after the addition is completed, continuously stirring the solution with magnetic force at a temperature of 90° C. and evaporating the solution in a water bath to obtain iron sol; S4, sending the iron sol into a reactor, and performing a hydrothermal treatment for 2.5 hours under a pressure condition of 3.8 MPa and a temperature condition of 180° C., after the hydrothermal treatment, separating and filtering the solids, washing with water once, and drying with hot air at 110° C. to obtain a magnetic core material; S5, 1,4-benzenedicarboxaldehyde, azo(2-amidinopropane) dihydrochloride, methacryloyloxyethyltrimethylammonium chloride, acrylamide and deionized water are mixed evenly in a beaker, heated to 45° C., ammonium persulfate and magnetic core material are added, kept warm, and ultrasonically homogenized at a power of 400 W for 15 min to obtain a first mixture; S6, heating the first mixture to 60° C., and irradiating the first mixture with ultraviolet light for 2 h using an ultraviolet light source with a wavelength of 254 nm and a power of 600 W under simultaneous stirring and heat preservation; S7, separating and filtering the solids, washing with acetone twice, washing with water twice, and drying with hot air at 110° C. to obtain magnetic particles; S8, mixing the magnetic particles, tetraethyl orthosilicate, anhydrous ethanol and deionized water in a beaker to obtain a silicon source suspension; S9, by dropping 12% sulfuric acid aqueous solution into the silicon source suspension and stirring, the pH value of the silicon source suspension is adjusted to 4, and the magnetic stirring is continued at a speed of 200 rpm / min for 2.5 hours to obtain a silica sol containing magnetic particles; S10, soaking the silica sol in anhydrous ethanol for aging for 24 hours to obtain a silica gel containing magnetic particles; S11, using carbon dioxide as a medium, at a temperature of 32° C. and a pressure of 7.4 MPa, supercritically drying the silica gel to obtain a porous carrier; S12, dissolving ammonium dihydrogen phosphate in deionized water, adding a porous carrier, and ultrasonically treating at a power of 400 W for 30 minutes to obtain a catalyst suspension; S13, evaporating the catalyst suspension to dryness, washing the solid twice with water and drying it with hot air at 110°C to obtain a solid catalyst.
[0045] Table 1 Comparative Example 1 In this comparative example, a solid catalyst sample 5 was prepared, and its raw material ratio is shown in Table 2. Its preparation process is as follows: S1. Mix KH550 aminopropyl triethoxysilane, xanthan gum, anhydrous ethanol and deionized water in a beaker, gradually add ferric nitrate and stir magnetically at a speed of 300 rpm / min until the pH reaches 5 to obtain an iron salt solution; S2, mixing sodium hydroxide and deionized water to prepare an 8wt% alkaline solution; S3, adding alkaline solution to the iron salt solution and continuously stirring the solution with magnetic force at a speed of 180 rpm / min until the pH value is 9, and after the addition is completed, continuously stirring the solution with magnetic force at a temperature of 90° C. and evaporating the solution in a water bath to obtain iron sol; S4, sending the iron sol into a reactor, and performing a hydrothermal treatment for 2.5 hours under a pressure condition of 3.8 MPa and a temperature condition of 180° C., after the hydrothermal treatment, separating and filtering the solids, washing with water once, and drying with hot air at 110° C. to obtain a magnetic core material; S5, mixing azo(2-amidinopropane) dihydrochloride, methacryloyloxyethyltrimethylammonium chloride, acrylamide and deionized water in a beaker, heating to 45° C., adding ammonium persulfate and magnetic core material, keeping warm, and ultrasonically homogenizing at a power of 400 W for 15 min to obtain a first mixture; S6, heating the first mixture to 60° C., stirring the mixture with magnetic force at a speed of 400 rpm / min and keeping the temperature for 2 h; S7 to S13 are the same as those in the first embodiment.
[0046] Table 2 Comparative Example 2 In this comparative example, a solid catalyst sample 6 was prepared, and its raw material ratio was the same as that of sample 1 in Example 1, and its preparation process was as follows: S1 to S5 are the same as in Embodiment 1; S6, heating the first mixture to 60° C., stirring the mixture with magnetic force at a speed of 400 rpm / min and keeping the temperature for 2 h; S7 to S13 are the same as those in the first embodiment.
[0047] Embodiment 2 In this embodiment, a series of phenyl silicone oil samples were prepared, and the raw material ratios thereof were shown in Table 3. The preparation process thereof was as follows: S1. Add dehydrated trimethyltriphenylcyclotrisiloxane and solid catalyst into the first reaction device, heat to 55° C. and stir evenly; S2, adding 50% of the total amount of diphenyl double end cap, heating to 75°C and stirring for 2.5 hours to perform prepolymerization to obtain a prepolymer; S3. Under nitrogen protection, the prepolymer and the solid catalyst are transferred to the second reaction device, the remaining 50% of the diphenyl double-end is added, the temperature is raised to 100° C., and the mixture is stirred and reacted for 3 hours to allow the prepolymer to undergo a ring-opening copolymerization reaction; S4. After the ring-opening copolymerization reaction is completed, the pH value is adjusted to 7, and the solid catalyst is recovered to obtain a copolymer; S5, allowing the copolymer to stand for 3 hours and stratify; S6, distilling the copolymer under reduced pressure at 205° C. under a vacuum condition of −0.08 Mpa to remove low-boiling substances, thereby obtaining a special phenyl silicone oil; The performance test parameters of the phenyl silicone oil sample prepared in this example are shown in Table 3.
[0048] Table 3 Accelerated testing In order to measure the recycling performance of the catalyst, the present invention further implements an accelerated test, and the test method of the accelerated test is as follows: S1, according to the mass ratio of trimethyltriphenylcyclotrisiloxane: diphenyl double end: solid catalyst = 100:5:3, solid catalyst samples 1 to 6 are used as solid catalysts, and phenyl silicone oil is prepared by the steps of Example 2; S2, after each reaction is completed, the solid catalyst is recovered by magnetic separation, and the same solid catalyst sample is used to repeat the above reaction step S1 20 times; S3, for the last reaction in the cyclic execution step of S2 above, the yield of phenyl silicone oil in this reaction was tested, and the test results are shown in Table 4.
[0049] Table 4 Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a special phenyl silicone oil for cosmetics, characterized in that: The preparation method comprises: S110, performing a prepolymerization reaction using raw materials including trimethyltriphenylcyclotrisiloxane, diphenyl double end cap, and a solid catalyst to obtain a prepolymer; S120, adding the diphenyl double end cap to the prepolymer again to carry out a ring-opening copolymerization reaction to obtain a copolymer; S130, distilling the copolymer under reduced pressure to remove low-boiling substances to obtain the special phenyl silicone oil; Wherein, the solid catalyst is prepared by the following steps: S210, preparing a magnetic core material containing anionic polymer; S220, coating the surface of the magnetic core material with an organic substance containing a cationic polymer to obtain magnetic particles; S230, using a raw material including the magnetic particles to prepare a porous silica carrier; S240, loading ammonium dihydrogen phosphate on the silica porous carrier to obtain the acidic solid catalyst.
2. The preparation method according to claim 1, characterized in that: In terms of mass ratio, trimethyltriphenylcyclotrisiloxane: diphenyl dicapped: solid catalyst = (80-100): (2-6): (1-3).
3. The preparation method according to claim 1, characterized in that: S110 specifically includes: S111, adding the dehydrated trimethyltriphenylcyclotrisiloxane and the solid catalyst to the first reaction device, heating to 50° C. to 60° C. and stirring evenly; S112, adding the diphenyl double head accounting for 40% to 60% of the total addition amount, raising the temperature to 70° C. to 75° C. and stirring the reaction for 2 h to 3 h to carry out the prepolymerization reaction to obtain the prepolymer.
4. The preparation method according to claim 1, characterized in that: S120 specifically includes: S121, under the protection of inert gas, transferring the prepolymer and the solid catalyst to a second reaction device, adding the remaining diphenyl double end, raising the temperature to 100° C. to 105° C., and stirring the reaction for 3 h to 4 h to allow the prepolymer to undergo the ring-opening copolymerization reaction; S122. After the ring-opening copolymerization reaction is completed, the pH value is adjusted to neutral, and the solid catalyst is recovered to obtain the copolymer.
5. The preparation method according to claim 1, characterized in that: S130 specifically includes: S131, allowing the copolymer to stand and separate into layers; S132, distilling the copolymer under reduced pressure at 200° C. to 210° C. under a vacuum condition of -0.15 MPa to -0.05 MPa to remove low-boiling point substances, thereby obtaining the special phenyl silicone oil.
6. The preparation method according to any one of claims 1 to 5, characterized in that S210 specifically includes: S211, uniformly mixing the aminopropyl triethoxysilane, the xanthan gum, the ethanol and the water in a mass ratio of aminopropyl triethoxysilane: xanthan gum: ethanol: water = (1-2): (2-4): (5-10): 100, gradually adding ferric nitrate and stirring until the pH reaches 5, to obtain an iron salt solution; S212, mixing the 1,4-diaminobenzene in the ethanol in a mass ratio of 1,4-diaminobenzene: sodium hydroxide: ethanol: water = (2-4): (8-10): (10-20): 100, adding the sodium hydroxide and the water and mixing again to obtain an alkaline solution; S213, adding the alkaline solution dropwise to the iron salt solution and continuously stirring until the pH value reaches 9, and after the addition is completed, stirring the iron salt solution at a temperature of 85° C. to 95° C. and evaporating in a water bath to obtain an iron sol; S214, sending the iron sol into a reactor, and performing a hydrothermal treatment for 2.5 hours to 3 hours under a pressure condition of 3Mpa to 5Mpa and a temperature condition of 180°C to 190°C. After the hydrothermal treatment, separating and filtering the solids, washing, and drying to obtain the magnetic core material.
7. The preparation method according to claim 6, characterized in that: S220 specifically includes: S221, according to the mass ratio of ammonium sulfate: 1,4-benzenedicaldehyde: azo(2-amidinopropane) dihydrochloride: methacryloyloxyethyl trimethyl ammonium chloride: acrylamide: magnetic core material: water = (0.2-0.3): (0.4-1.2): (1-2): (6-8): (6-8): (20-25): 100, 1,4-benzenedicaldehyde, the azo(2-amidinopropane) dihydrochloride, the methacryloyloxyethyl trimethyl ammonium chloride, the acrylamide and water are mixed uniformly, heated to 45° C. to 50° C., and then the ammonium persulfate and the magnetic core material are added, kept warm and mixed uniformly again to obtain a first mixture; S222, heating the first mixture to 55° C. to 60° C., and irradiating the first mixture with ultraviolet light for 1.5 h to 2 h using an ultraviolet light source with a wavelength of 254 nm to 365 nm and a power of 600 W to 800 W under simultaneous stirring and heat preservation; S223, after the heating treatment and the ultraviolet light irradiation treatment are completed, the solid matter is separated and filtered, washed, and dried to obtain the magnetic particles.
8. The preparation method according to claim 6, characterized in that: S230 specifically includes: S231, mixing the magnetic particles, the tetraethyl orthosilicate, the ethanol and the water in a mass ratio of magnetic particles: tetraethyl orthosilicate: ethanol: water = (10-15): (30-50): (30-50): 100 to obtain a silicon source suspension; S232, by dropping a sulfuric acid aqueous solution into the silicon source suspension and stirring, the pH value of the silicon source suspension is adjusted to 4 to 5, and the stirring is continued for 2.5 hours to 3 hours to obtain a silica sol containing the magnetic particles; S233, soaking the silica sol in anhydrous ethanol for aging for 20 hours to 24 hours to obtain a silica gel containing the magnetic particles; S234. Using carbon dioxide as a medium, supercritically drying the silica gel at a temperature of 31° C. to 33° C. and a pressure of 7.3 MPa to 7.5 MPa to obtain the porous carrier.
9. The preparation method according to claim 8, characterized in that: S240 specifically includes: S241, dissolving the diammonium phosphate in the water at a mass ratio of diammonium phosphate: porous carrier: water = (25-30): (30-35): 100, adding the porous carrier, and uniformly dispersing by ultrasonication to obtain a catalyst suspension; S242, evaporating the catalyst suspension to dryness, washing and drying the solid matter to obtain the solid catalyst.
10. A special phenyl silicone oil for cosmetics, characterized in that: The special phenyl silicone oil is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A magnetic solid acid catalyst and its application in the catalytic fructose hydrolysis reaction
CN113663710B
Preparation method, product and application of a magnetic multi-component iron-carbon composite Fenton catalyst
CN114100634B
Fe3O4@SiO2 composite material adsorbent preparation method and application
CN102500336A
Preparation method and detachment method of detachable magnetic-microsphere-supported noble metal catalyst
CN106111210A
Preparation method of 2-thiouracil modified porous magnetic xanthan gum micro-spheres
CN106902755A